DNA damage in grasshopper Chorthippus brunneus (Orthoptera) hatchlings following paraquat exposure. (April 2015) - Augustyniak, M.; Nocoń, Ł.; Kędziorski, A.; Łaszczyca, P.; Sawczyn, T.; Tarnawska, M.; Zawisza-Raszka, A.
Highlights: Paraquat (PQ) caused immediate DNA damage in brain cells of grasshopper's hatchlings. DNA damage following paraquat treatment was significantly dose-dependent. PQ applied in vivo may cross blood–brain barrier in the grasshopper's hatchlings. Abstract: Comet assay was applied to study genotoxic damage induced by paraquat (PQ) in brain cells of Chorthippus brunneus (Insecta: Orthoptera) hatchlings. Percentage of the comet fluorescence in the tail (TDNA), length of the comet tail (TL) and Olive tail moment (OTM) were used for quantitative assessment of the DNA damage. Multiple regression analysis supplemented standard statistical elaboration of the results. Increasing PQ concentrations applied either directly to the brain cells suspension (10, 50, and 250 μM PQ final concentration – in vitro protocol) or indirectly (50, 250, and 1250 μM PQ final concentration – in vivo protocol) provoked significant increase of oxidative damage to DNA (higher median TDNA and OTM values). The damage increased with time of exposure (0, 5, 15, and 30 min) following in vitro application, but decreased in longer interval (3 vs 24 h) after in vivo administration of paraquat. On contrary, median TL values did not correlate with paraquat concentration irrespectively of the exposure protocol. Possible reason of this discrepancy in light of paraquat toxicity is discussed.